2018
DOI: 10.1177/2156759x19852617
|View full text |Cite
|
Sign up to set email alerts
|

New School Counselors’ Perceptions of Factors Influencing Their Roles as Leaders

Abstract: This qualitative study explored the experiences of new school counselors in establishing themselves as leaders in their schools. Specifically, it focused on factors this population perceives as promoting or impeding their role as leaders. We interviewed 12 participants in their first through third year as school counselors. Four themes emerged from the data including intrapersonal factors, sociocultural factors, systemic factors, and interactive factors. We discuss implications for counselor educators, distric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 33 publications
0
12
2
Order By: Relevance
“…The results concerning age as a significant predictor to school counselors’ leadership practices suggest that as school counselors increase in age, they are more likely to engage in such practices. This seems to be both supported (Mason & McMahon, 2009; Mullen et al, 2019; Robinson et al, 2019) and challenged (e.g., Lowe et al, 2017) by the extant school counseling leadership literature. For instance, Mason and McMahon’s (2009) results indicated that older school counselors were more likely to engage in leadership practices, whereas Lowe et al’s (2017) results suggested that age and years of experience were nonsignificant predictors of transformational leadership practice.…”
Section: Discussionmentioning
confidence: 80%
See 4 more Smart Citations
“…The results concerning age as a significant predictor to school counselors’ leadership practices suggest that as school counselors increase in age, they are more likely to engage in such practices. This seems to be both supported (Mason & McMahon, 2009; Mullen et al, 2019; Robinson et al, 2019) and challenged (e.g., Lowe et al, 2017) by the extant school counseling leadership literature. For instance, Mason and McMahon’s (2009) results indicated that older school counselors were more likely to engage in leadership practices, whereas Lowe et al’s (2017) results suggested that age and years of experience were nonsignificant predictors of transformational leadership practice.…”
Section: Discussionmentioning
confidence: 80%
“…Specifically, we employed ESC to explore four levels of ecological factors in relation to school counselors' leadership practices. Despite the limited empirical evidence for the ESC framework, some school counseling studies appear to have organized their results within an ecological framework (e.g., Robinson et al, 2019).…”
Section: Ecological Factorsmentioning
confidence: 99%
See 3 more Smart Citations